Analysis of vaginal microbiota before and after treatment of high-grade squamous intraepithelial lesions of the uterine cervix - Patrícia Mendonça Ventura; Isabel Cristina Chulvis do Val Guimarães; Luis Guillermo Coca Velarde; Susana Cristina Aidé Viviani Fialho; Douglas Guedes Ferreira; Matheus Madureira Fernandes; Rafael Augusto Chaves Machado (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective: HPV infection is considered the most common sexually transmitted virus today. The persistence of HPV is the main cause for the development of precursor lesions and cervical cancer. There are environmental and non-environmental factors that contribute to the persistence of the virus. Studies indicate a possible relationship between the vaginal microbiota (environmental factor) and the risk of high-grade cervical squamous intraepithelial lesions and cervical cancer. This study evaluates the association between the type of vaginal microbiota and the occurrence of high-grade squamous intraepithelial lesions of the cervix. Methods: Observational, longitudinal, prospective, and analytical studies carried out between 2019 and 2021, which evaluated the vaginal microbiota of patients diagnosed with high-grade cervical squamous intraepithelial lesion before and after treatment in two collections with an interval of 6 months, using scrapings and vaginal swabs. Results: In Group I (with lesions) 28 women participated and 29 in Group II (without lesions). According to Nugent, in the initial collection of Group I, 16 women (57%) had lactobacillary microbiota, eight (28%) intermediate, and four (14%) coccus. In Group II, twenty-one (75%) were lactobacillary, one (3%) was intermediate, and seven (24%) werecoccus. With p=0.03. Conclusion: According to Nugent's criteria, there was an association between the type of vaginal microbiota and the occurrence of high-grade cervical squamous intraepithelial lesions of the cervix. The same was not observed in the Donders classification. Studies with a larger sample are needed to confirm our results.